Implementation of Citizenship Project-Based Learning Model to Strengthening Student Responsibility Character in Pancasila Courses - Tika Amanda; Sunarso Sunarso; Mukhamad Murdiono; Annisa Istiqomah (Riviera Publishing, 2024)
Universities must adapt to 21st-century skills, emphasizing character education to foster holistic student development. This study aimed to enhance students' character of responsibility in the Pancasila course through the Citizenship Project-Based Learning (CPBL) model. Employing the Classroom Action Research (CAR) method, the study involved planning, action, observation, and reflection stages, with data collected via observations and questionnaires and analyzed descriptively. The CPBL model significantly improved students' ability to take responsibility for individual and group tasks, solve problems, provide solutions, and deliver effective project presentations. Students showcased enhanced critical thinking, teamwork, accountability in task completion, and creative problem-solving, as reflected in group portfolios and video presentations. The learning process fostered higher engagement, collaboration, and the development of a responsible character aligned with Pancasila values. This study highlights the CPBL model's potential as a practical framework for integrating character education into higher education. It strengthens critical thinking and collaboration and equips students with the competencies necessary for societal contribution and national development. The model offers a replicable approach to embedding Pancasila values in educational practices, making it a valuable tool for fostering responsibility and holistic character development in university students.